Silent Players : a Biographical and Autobiographical Study of 100 Silent Film Actors and Actresses. - Slide, Anthony (University Press of Kentucky, 2010)
"From his unique perspective of friendship with many of the actors and actresses about whom he writes, silent film historian Anthony Slide creates vivid portraits of the careers and often eccentric lives of 100 players from the American silent film industry. He profiles the era's shining stars such as Lillian Gish and Blanche Sweet; leading men including William Bakewell and Robert Harron; gifted leading ladies such as Laura La Plante and Alice Terry; ingénues like Mary Astor and Mary Brian; and even Hollywood's most famous extra, Bess Flowers. Although each original essay is accompanied by s.